Pemberdayaan Masyarakat Desa Pada Sektor Pendidikan Di Distrik Kuala Kencana Kabupaten Mimika Provinsi Papua - Wakerkwa, Gerson (JURNAL ILMIAH SOCIETY, 2015)
Empowerment of rural communities in the education sector is the policy of national community empowerment program implemented by the government incessantly , especially in rural communities various sectors . Reality shows in the implementation of the program in the district of Kuala Kencana Pemberdyaan optimally yet felt by the villagers .By using qualitative descriptive approach was found that the cause of empowerment of rural communities in the education sector in the district of Kuala Kencana less than optimal due to lack of awareness of the importance of education , and the awareness of parents to send children still lacking because of the constraints of social status and economic factors of society . Empowerment requires educators who are able , followed by infrastructure , the availability and the need to implement programs for the empowerment of the education sector in accordance with the aspirations of the community to develop the potential that exists.Â Keywords : Empowerment , Community , Education